PEMAKNAAN FIKIH TERHADAP HAK ANAK SETELAH MENINGGAL DUNIA DAN IMPLIKASINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Akbar Rahman; Dwi Suci Siska Sari; Idham Kholid; Fachrul Ghazi; Erlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines the fiqh-based interpretation of children’s rights after death and its implications for Islamic Religious Education. In Islamic jurisprudence, children who pass away retain certain rights that must be fulfilled by parents and the community, including ritual care such as bathing, shrouding, funeral prayer, burial, and the right to prayers and protection of dignity. However, in educational and social practices, the understanding of children’s posthumous rights is often limited to ritual aspects without exploring their educational values. This study employs a qualitative approach through library research by analyzing classical and contemporary fiqh sources as well as relevant literature on Islamic Religious Education. The findings reveal that the fiqh interpretation of children’s rights after death encompasses not only ritual obligations but also theological, moral, and pedagogical values that are essential to be integrated into Islamic education. The implications suggest that Islamic Religious Education should incorporate these fiqh concepts to cultivate empathy, responsibility, respect for human dignity, and awareness of the afterlife among learners. This study contributes to the enrichment of Islamic Religious Education by offering a value-based and character-oriented educational perspective.